Amélioration des taux de multiplication chez deux clones d’artichaut (Cynara Scolymus L.) Le violet d’Alger et le violet hyérois. - BELAID, Mourad; BENGHAOUAL, Charef (My University, 2019)
The artichoke (Cynara scolymus L.) is largely cultivated all around the world. In Algeria, this species valorizes efficiently heavy soils and sodium chloride water charged, occurring frequently in the low valley of chéliff, where this culture cultivated. However, this species presents a very complex mode of sexual reproduction and vegetative multiplication is until now the only way of multiplication, for production as well as for selection. However, even this way of multiplication is confronted with two major problems, which limit the extension and the development of this culture: the low propagation ratio and viral diseases. Such problems can only be solved by improving the multiplication rates as conceived by our test.
Keywords: Artichoke; Vegetative multiplication; Improvement of multiplication rates